Wind turbine power coefficient real-time identification. (6th April 2009) - Monroy, A.; Alvarez-Icaza, L.
A scheme for real-time identification of a wind turbine power coefficient curve is presented. Knowledge of this curve is important to maximise the generated electric power. The precise shape of this curve is difficult to predict as it depends on several factors: air density, humidity, temperature, wind speed and tip speed. Once the power coefficient curve is found, it is possible to propose reference power points appropriate for the turbine mode of operation that are fed to a controller of the electric generator. Two models for this surface are proposed whose parameters can be identified in real-time. The first model considers variations on the blade angle and the other is a simplified model useful for variable speed wind turbines. Simulation results show good performance of this identification scheme.